An analysis of accessibility in architectural design in terms of wheel chair users - İskender, Emine; TÜRKYILMAZ, EMRAH (My University, 2018)
Although legal rights of people with disabilities are known in Turkey, studies are insufficient on rearrangement of built environment in the fashion to serve physical accessibility of people with disabilities. This study aims to review legal rights of individuals with disabilities, within the current system in Turkey and to introduce rearrangements which enable indoor accessibility for people with disabilities. To that end, minimum requirements to enable physical indoor accessibility for individuals with disabilities were identified by examining the standards set forth by TS 9111 The Requirements of Accessibility in Buildings for People with Disabilities and Mobility Constraints, and those requirements were analyzed in terms of selected model projects. Within the scope of this research, indoor accessibility for individuals with disabilities who use wheelchair was addressed, and analyses on model projects were performed by checking requirements of wheelchair users. Following the analyses, accessibility of selected model projects was determined, and deductions were made on how designing process must be performed by taking minimum requirements into consideration.
Keywords: Accessibility in Architectural Design; Disability; Wheel Chair Users; Mimari Tasarımda Erişilebilirlik; Sakatlık; Tekerlekli Sandalye Kullanıcıları